“Saber e ser médico e o desafio de aprender a ser gestor”: a prática dialógica dos gestores médicos - Lewandowski, Maiane Bertoldo (Universidade do Vale do Rio dos Sinos, 2014)
In the hospital organizations, the division between areas purposes (business) and middle areas (administrative), affects the management between two bodies, managers and administrative specialists managers. Historically, physicians have been occupying executive positions in these institutions, however, be a manager usually not a desire or motivation for physicians, who find their recognition in the medical specialty chosen. In contrast, hospitals, at the same time, have the challenge of forming constitute identity and develop leaders (technical people) in the pursuit of value creation. Therefore, this study sought to identify and analyze what elements are necessary for the preparation of medical and hospital organizations in situations where the former are assigned to executive functions. To that end, the research is exploratory, with the strategy fieldwork. Semi-structured qualitative interviews were conducted with 21 medical managers working in hospitals connected to ANAHP - National Association of Private Hospitals. These institutions of private health cover four Brazilian states: RS, SP, MG and DF. All interviews were audio-recorded, transcribed into text and categorized, and organized and analyzed using the qualitative research software NVivo ® 10. For discussion and interpretation of research data, we used content analysis, encompassing discursive textual analysis. The results were organized into four units of analysis: integrating medical officer in the hospital culture, understanding of the empowerment of physicians in executive functions process, discussion of professional identity of medical officer and signaling factors and practices that contribute to retention and performance of medical executive functions. The medical officer understands and recognizes before this identity process (from doctor to doctor manager), but has insecurities are fully recognized in the management function, as occurs with conventional executives because the circuit identity is through their recognition as doctor. Linear executive empowerment in other areas, such as administration, does not occur in the same way with the medical officers, who regard accepted the position as recognition and gratitude (presence of personal values) and not as an option or choice of career. Thus, this research highlighted the contributions spanned academia, the business community and medical managers themselves.
Keywords: Gestores médicos; Instituições hospitalares; Liderança; Identidade ampliada; Gestão estratégica de pessoas; Carreira paralela; Medical managers; Hospital organizations; Lead; Identity extended; Strategic people management; Parallel career; ACCNPQ::Ciências Sociais Aplicadas::Administração